Analisis Kesadaran Metakognisi Siswa Dalam Pembelajaran Garis Dan Sudut Melalui Asesmen Pemecahan Masalah Matematika - Maharani, Noka setya; Irfan, Muhammad (Jurnal Pendidikan dan Teknologi Pembelajaran Matematika, 2025)
This study aims to describe the metacognitive awareness of grade VII junior high school students in learning lines and angles through mathematical problem solving assessments. This study is a quantitative descriptive study with a pre-experimental design and a One Group Posttest Design. The sample size was 32 students with purposive sampling. Data collection through tests and non-tests. Test data were obtained from problem-solving ability test data on line and angle material. Non-test data were obtained from the Metcognitive Awareness Inventory questionnaire filled out by students after working on problem-solving questions to determine students' metacognitive awareness in problem solving. The results of this study indicate that 56% of students have moderate metacognitive awareness, 25% of students have high metacognitive awareness, and 19% of students have low metacognitive awareness. The conclusion of this study is that metacognitive awareness is one of the important aspects that students must have, so it needs to be trained to students in the learning process in the classroom so that students have good metacognitive awareness, which will help students in problem solving